Chair of tears - Vizenor, Gerald Robert, 1934- (Native storiers., 2012)
"The novel begins with generous stories about Captain Eighty, his young wife, the poker-playing genius named Quiver, and their children and grandchildren who live on a rustic houseboat. Captain Shammer, an extraordinary grandson reared on the houseboat and with no formal education, is appointed the chairman of a troubled Department of Native American Indian Studies at a prominent university. Shammer is a natural enterpriser and ironic showman in the tradition of trickster stories. He arrives at the first faculty meeting dressed in the uniform of Gen. George Armstrong Custer. Native students celebrate his conversion of the department into an academic poker parlor and casino, and a panic radio station. The most sensational enterprise is the training of service mongrels to detect the absence of irony."--Page 4 of cover.